Sequential lineup presentation: patterns and policy - Lindsay, Rod C. L. (Legal and criminological psychology, 2009)
Sequential lineups were offered as an alternative to the traditional simultaneous lineup. Sequential lineups reduce incorrect lineup selections; however, the accompanying loss of correct identifications has resulted in controversy regarding adoption of the technique. We discuss the procedure and research relevant to (1) the pattern of results found using sequential versus simultaneous lineups; (2) reasons (theory) for differences in witness responses; (3) two methodological issues; and (4) implications for policy decisions regarding the adoption of sequential lineups.